2008
DOI: 10.1515/biomat.2008.9.1-2.18
|View full text |Cite
|
Sign up to set email alerts
|

No Adaptations in Bone of Leptin-Deficient ob/ob Mice in Response to Loading

Abstract: Leptin is a peptide hormone produced predominantly by white fat cells [1,47]. The mature protein, encoded by the obesity (ob) gene localized in human and mouse 7 and 6 chromosomes, respectively, is a 16 kDa non-glycosylated protein. Leptin levels in the blood are proportional to adipose tissue mass. Initially discovered as a central regulator of appetite and energy expenditure, leptin levels can be considered as a signal to the body regarding its energy reserves. Although elevated leptin levels are present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…Fogelholm et al showed that the bone mineral density in the non-weight bearing bone of the distal radius was more strongly correlated with body weight than bone mineral density in the weight-bearing bones of the hip and spine 2. In our study we have shown the discrepancy in bone formation in the limbs and spine 3. This suggests that first body fat regulates bone metabolism by means of hormonal factors, and second the effects of muscle and loading are signaling factors in mechanotransduction 4, 5.…”
Section: Introductionsupporting
confidence: 53%
“…Fogelholm et al showed that the bone mineral density in the non-weight bearing bone of the distal radius was more strongly correlated with body weight than bone mineral density in the weight-bearing bones of the hip and spine 2. In our study we have shown the discrepancy in bone formation in the limbs and spine 3. This suggests that first body fat regulates bone metabolism by means of hormonal factors, and second the effects of muscle and loading are signaling factors in mechanotransduction 4, 5.…”
Section: Introductionsupporting
confidence: 53%
“…In our own studies we were able to demonstrate differences in trabecular bone 41, 42 and the histomorphological progress of osteoarthritis in ob/ob-mice 43.…”
Section: Introductionmentioning
confidence: 68%